Citotoxicidade de três cimentos de uso endodôntico em células L 929 - Pinheiro, Rosangela Acris (2007)
The procedure of this in vitro research based itself on the evaluation of the cytotoxicity of three sealers of endodontic use, epoxic resin base: Sealer 26®, AH Plus® and Acroseal®. To such an experiment, after 48 h of manipulation were accomplished by the agar diffusion methodology associated to the red neutral colorant on cells L-929, trough the seeding in appliance of six cavities. After 24 hour in a heater humidificated at 37ºC with 5% of CO2, a clear halo could be seen around the samples and the positive controls, elating to the specimens cytotoxicity of the sealers. The measurement was made according to Operational Protocol Standard POP/FIOCRUZ. All the sealers presented cytotoxicity, but the AH PLUS® sealer showed the best biological behavior, estimating the lowest cytotoxicity index followed by the Sealer 26® and Acroseal® which presented the worse index of biological reactivity. The statistics data were estimated by the application of ANOVA and Student-Newman tests, p<0,05.